Disaster Preparedness and Response (Comparison Between Delhi, Mussoorie and Kerala) - Savvy Jain; Avitesh Vaishnavi Nayak (International Journal of Urban Design and Development, 2025)
Disaster preparedness and response are critical for minimizing the adverse impacts of natural and man-made disasters. These practices play a crucial role in saving lives, reducing economic losses, and ensuring the resilience and recovery of communities. By prioritizing preparedness and response, societies can build resilience against the inevitable occurrence of natural and man-made disasters. This comparative analysis examines the distinct strategies employed by Delhi, Mussoorie, and Kerala, highlighting how each region addresses its unique set of challenges. Comparing these three regions reveals distinct approaches shaped by their unique geographical and socio-economic contexts. Delhi's emphasis on technology and infrastructure reflects its urban complexity and the need for robust, rapid-response systems. Mussoorie's focus on local coordination and preventive measures highlights the importance of community resilience in remote, disaster-prone areas. Kerala's comprehensive, community-based approach showcases the effectiveness of integrating advanced warning systems with grassroots involvement, providing a model for holistic disaster management. Each region demonstrates effective strategies tailored to their specific vulnerabilities. These varied approaches underscore the importance of context-specific disaster preparedness and response plans, illustrating that while challenges differ, the core principles of resilience, community involvement, and proactive planning are universally applicable. As climate change exacerbates natural disasters globally, the lessons from these regions can inform broader strategies to enhance disaster preparedness and response worldwide.
Keywords: Climate change; Sustainability; community; disaster; resilience